An Evaluation of the Nutritional Value and Physical Properties of Blenderised Enteral Nutrition Formula: A Systematic Review and Meta-Analysis - Ojo, Omorogieva; Adegboye, Amanda Rodrigues Amorim; Ojo, Osarhumwese Osaretin; Wang, Xiaohua; Brooke, Joanne (Nutrients, 2020)
Background: Although there are merits in using commercial “enteral nutrition formula” (ENF) compared with blended ENF, there is a growing preference for the use of blended ENF in many countries globally. However, the nutritional value and physical properties of blended ENF compared with commercial ENF may be limiting its use. We have not found any evidence of a meta-analysis on the nutritional value of blended diets in the adult population. Aim: The aim of this review was to compare the nutritional value, physical properties, and clinical outcomes of blended ENF with commercial ENF. Methods: The preferred reporting items for systematic reviews and meta-analyses were used for this review. The search strategy was based on a Population, Intervention, Comparator, Outcome framework. The following databases; Pubmed, EMBASE, PSYCInfo, and Google scholar were searched for articles of interest using keywords, Medical Subject Heading (MeSH) and Boolean operators (AND/OR) from the inception of each database until 23 February 2020. The articles were evaluated for quality. Results: Based on the systematic review and meta-analysis, four distinct themes were identified; Nutritional value, Physical properties, Clinical outcomes; and Adverse events. The findings of this review showed inconsistencies in the macronutrient and micronutrient values of the blenderised ENF compared with the commercial ENF. The results of the meta-analysis demonstrated that there were no significant differences (p > 0.05) between the blenderised ENF and the commercial ENF in relation to the fat and protein contents of the diets. However, the blenderised ENF was significantly lower (p < 0.05) than the commercial ENF regarding the energy content of the diets, with an overall mean difference of −29.17 Kcal/100 mL (95% CI, −51.12, −7.22) and carbohydrate content with an overall mean difference of -5.32 g/100 mL (95% CI, −7.64, −3.00). In terms of sodium, potassium, and vitamin A, there were no significant differences (p > 0.05) between the blenderised and commercial ENF, although significant differences (p < 0.05) were observed between the two diets with respect to calcium, phosphorus, magnesium, zinc, iron, and vitamin C contents. Furthermore, the blenderised ENF showed significantly higher levels (p < 0.05) of viscosity and osmolality than the commercial ENF. The significantly lower levels of some of the macro-nutrients and micro-nutrients in the blenderised ENF compared with the commercial ENF and the difference in the expected nutritional values may be due to the fact blenderised ENF is produced from common foods. Thus, the type of foodstuffs, cooking, and processing methods may lead to loss of nutrients and energy density. The deficits in the energy content and some of the macro- and micro-nutrients in the blenderised ENF compared with commercial ENF may have implications for patients’ health and clinical outcomes. The clinical implications of the underdelivering of nutrients may include increased risk of undernutrition, including energy malnutrition, which could have a negative effect on body composition and anthropometric parameters, morbidity, mortality, length of hospital stay, and costs. For outpatient care, this could increase the risk of hospital re-admission and homecare costs. Additionally, the higher viscosity and osmolality of the blenderised ENF compared with the commercial ENF can increase the risk of complications, including tube blockage, and impaired delivery of feed, water, and medications, with significant implications for patients’ nutritional status and health outcomes. Conclusion: The results of this systematic review and meta-analysis identified significant variability in the nutritional value of blenderised ENF compared with commercial ENF. Furthermore, the nutritional values of the blenderised ENF do not meet the expected recommended levels compared with commercial ENF and these may have implications for patients’ nutritional status and health outcomes, including the effect on body composition, morbidity, mortality, hospital re-admission, and costs. Further studies are needed to elucidate the nutritional value of blenderised ENF on patients’ clinical outcomes.